Ticks and tick-borne pathogens at the interplay of game and livestock animals in South Africa - Berggoetz, Mirko (My University, 2013)
Nous avons étudié les pathogènes transmis par les tiques en Afrique du Sud (Free State, Mpumalanga, Gauteng et Limpopo), plus précisément, l’échange de pathogènes se produisant entre ongulés sauvages et domestiques. Un total de 7364 tiques appartenant à 13 espèces a été récolté sur 181 hôtes. Les protozoaires Babesia et Theileria ainsi que les bactéries Anaplasma et Ehrlichia ont été recherchés dans le sang des hôtes et dans les glandes salivaires des tiques par PCR, « Reverse Line Blot » et séquençage. Un maximum de dix tiques mâles et de dix tiques femelles de chaque espèce a été analysé pour chacun des individus, soit 2117 tiques. Celles-ci présentaient un taux d’infection de 15% comprenant 397 infections appartenant à 23 espèces de pathogène. Quant aux hôtes vertébrés, près de 61% d’entre eux étaient infectés par 16 espèces de pathogène. Ce travail a permis d’observer des infections non encore décrites : 30 impliquant dix espèces de pathogènes chez les hôtes et 23 impliquant 14 espèces de pathogènes chez les tiques. L’analyse en composante principale (ACP) a permis d’attribuer les 163 infections dans le sang des hôtes à quatre groupes dont trois sont constitués des ovins, bovins et équidés domestiques et de leurs équivalents sauvages. Ces groupes représentent les voies privilégiées de transmission des pathogènes parmi et entre la faune sauvage et les animaux domestiques. Les glandes salivaires des tiques des hôtes sauvages (n=64) présentent des taux et des densités d’infection significativement plus élevés que celles des tiques des animaux domestiques (n=64) vivant à proximité. Les animaux sauvages sont donc davantage exposés aux pathogènes se transmettant par les tiques que les animaux domestiques. Pourtant, l’infection du sang (prévalence et densité d’infection) n’est pas différente chez les animaux sauvages et domestiques exposés à ces mêmes tiques. La faune sauvage semble donc plus réfractaire aux pathogènes véhiculés par les tiques que les animaux de rentes. Néanmoins, les animaux sauvages et domestiques sont des sources d’infections tant pour eux-mêmes qu’entre eux. Cette étude apporte un éclairage nouveau sur les pathogènes transmis par les tiques à l’interface entre la faune sauvage et les animaux domestiques dans certaines régions d’Afrique du Sud., To evaluate the exposure of wild and domestic ungulates to tick borne-pathogens, and hence to study the pathogen exchange at the wildlife-livestock interface, blood from 181 individual hosts assigned to 18 species and 7364 ticks belonging to 13 species were collected. Samples originated from nine localities in four South African Provinces (Free State, Mpumalanga, Gauteng and Limpopo). Polymerase chain reaction followed by reverse line blotting and sequencing was used to screen host blood and tick salivary glands for protozoan pathogens of the genera Babesia and Theileria as well as for bacterial pathogens of the genera Anaplasma and Ehrlichia. From each individual infested host, a maximum of ten males and ten females of each tick species were dissected to isolate the salivary glands, this led to 2117 analysed ticks. Three hundred twenty nine ticks (15.5%), belonging to eight species, were infected and harboured 397 infections among which 57.7% were identified to species level and were assigned to 23 pathogen species. While, 110 / 181 individual hosts were infected and harboured 210 infections and 163 were identified to species level and belonged to 16 pathogen species. Screening such a large variety of host and tick species allowed describing 30 new host-pathogen combinations, involving ten pathogen species, and 23 new vector-pathogen combination which involved 14 pathogen species. Principal component analysis (PCA) assigned the 163 infections, identified to species level in host blood, to four groups. Three groups were associated to sheep, cattle and horses and their respective wild counterparts. Each group was characterized by high homogeneity in pathogen assemblage and host phylogenetic status. These groups characterized the most privileged transmission routes between and among wild and domestic ungulates. Within six localities, we sampled an equal number of wild and domestic animals (n = 128). On this dataset, once having controlled for the significant variation among localities, the infection prevalence and intensity of infection did not differ significantly between wild and domestic hosts. Interestingly, salivary glands from ticks infesting wild ruminants displayed significantly higher infection prevalence and pathogen mean density than salivary glands from ticks infesting livestock animals. This suggests that wild ungulates are more refractory to tick-borne pathogen infections than domestic ones, given that the infection prevalence and intensity of infection displayed similar values in host blood of wild and domestic ungulates. However, both animal types could act as equally efficient sources of infection for themselves and for each other. Overall, this study shed new light on the pathogen circulation naturally achieved at the interplay between wild and domestic ungulates.
Thèse de doctorat : Université de Neuchâtel, 2013
Keywords: Pathogènes; tiques; faune sauvage africaine; animaux de rentes; coinfections; Theileria; Babesia; Ehrlichia; Anaplasma; Tick-borne pathogens; African wildlife; Livestock; Co-infections; Theileria; Babesia; Ehrlichia; Anaplasma